Strain and composition dependence of orbital polarization in nickel oxide superlattices - Wu, Meng; Haverkort, Maurits W.; Lu, Yi (Physical review. B, Condensed matter and materials physics, 2013)
A combined analysis of x-ray absorption and resonant reflectivity data was used to obtain the orbital polarization profiles of superlattices composed of four-unit-cell-thick layers of metallic LaNiO3 and layers of insulating RXO3 (R=La, Gd, Dy and X=Al, Ga, Sc), grown on substrates that impose either compressive or tensile strain. This superlattice geometry allowed us to partly separate the influence of epitaxial strain from interfacial effects controlled by the chemical composition of the insulating blocking layers. Our quantitative analysis reveals orbital polarizations up to 25%. We further show that strain is the most effective control parameter, whereas the influence of the chemical composition of the blocking layers is comparatively small.